EXPLORATION OF MATHEMATICAL CONCEPTS IN THE LOCAL WISDOM OF THE MEKONGGA PEOPLE - Hidayati, Ully; Chairuddin, Chairuddin; Marillah, Dima (JME (Journal of Mathematics Education), 2025)
This study explores the mathematical concepts embedded in the cultural practices and local wisdom of the Mekongga people in Kolaka and East Kolaka Regencies, Southeast Sulawesi, Indonesia. Guided by an ethnomathematical perspective, the research aims to identify and describe how mathematical reasoning manifests through traditional architecture, art, rituals, and social systems. A qualitative approach with an ethnographic design was employed, involving purposive interviews with cultural informants such as the Deputy King of Mekongga, traditional artists, and Tolea (customary leaders). Data were collected through observation, interviews, documentation, and literature review, then analyzed using the Miles and Huberman interactive model consisting of data reduction, display, and conclusion drawing. The findings reveal that Mekongga culture embodies diverse mathematical ideas: set theory in cultural classification and royal genealogies; geometry and proportion in traditional houses; transformational geometry in woven fabrics and decorative motifs; plane geometry and ratio in the kalo sara symbol; social arithmetic in mahar (dowry) traditions; and alternative numeral systems in historical records. These results confirm that mathematical thought is inherently present within local wisdom and daily life. Theoretically, this study strengthens D’Ambrosio’s framework of ethnomathematics by demonstrating how indigenous practices represent mathematical reasoning. Pedagogically, it highlights the potential of Mekongga cultural elements as contextual and meaningful learning resources, bridging abstract mathematical concepts with cultural understanding in mathematics education.